Water Is Life Progress to secure safe water provision in rural Uganda - Fagan, G. Honor; Linnane, Suzanne; McGuigan, Kevin G.; Rugumayo, Albert I. (Practical Action Publishin, 2015)
This is a book about community-based research in the service of improving the sustainability and equity of safe water production, consumption, and management at community level in rural Uganda. It provides an account of the findings of a five-year combined social science, natural science, and engineering research work programme (2009–14) which took place within and with the community, in the sense that the community identified their water needs and related their everyday struggles with water resourcing to the research team, and they contributed to the outcomes. Our research programme began 14 years after the Ugandan government enacted the 1995 Water Statute (which provided the framework for the use, protection, and management of water resources and supply, the constitution of water authorities, and the devolution of water supply undertakings), 10 years after the 1999 National Water Policy was rolled out, and six years short of the delivery date for the Millennium Development Goals on water.